FITOREMEDIASI LIMBAH RUMAH TANGGA MENGGUNAKAN TUMBUHAN SEMANGGI AIR (Marsilea crenata) - Butarbutar, Yutrina; Ananda Pudan Simamora, Handika; Goreti Perawati, Maria; Tessalonika Napitu, Angel; Nilan Sari Rangkuti, Marlinda; Febriyossa, Adellia (Universitas Cokroaminoto Palopo, 2024)
Phytoremediation is an environmentally friendly technique that utilizes the ability of plants to absorb and break down pollutants. This study aims to evaluate the effectiveness of phytoremediation of (Marsilea crenata) plants in reducing pollutants in household waste. Experiments were conducted with variations in wastewater concentrations of 500 ml, 700 ml, 1000 ml, and 1200 ml, and control. The parameters observed included Total Dissolved Solids (TDS), pH, and temperature, which were measured on days 0, 2, 4, and 6. The results showed that treatment with Water Clover effectively reduced TDS, pH, and temperature levels of wastewater. At a concentration of 500 ml, TDS dropped by 79 ppm in 6 days. pH at 700 ml treatment dropped by 1.66 while temperature at 700 ml treatment dropped from 30.2°C to 26.8°C. The decrease in the value of these parameters shows that Marsilea crenata has great potential in improving the quality of household wastewater.